Comparative study of the impact of adjuvant trastuzumab and its biosimilars on cardiac function in HER2-positive early breast cancer patients: a single-center study - Au, Lok Sze Joyce; Luk, Mai Yee; Lee, Victor Ho Fun; Yuen, Kwok Keung (Frontiers in Oncology, 2025)
IntroductionTwo trastuzumab biosimilars have been introduced into the local public healthcare system since April 2021 as alternatives for treatment of human epidermal growth factor receptor (HER2) positive breast cancer. While their oncological efficacy compared to reference trastuzumab (Herceptin®) is well established, local comparative data on cardiotoxicity among the three formulations remain limited. This study evaluates the cardiac safety of Herzuma® and Kanjinti® compared with Herceptin® in a single-center cohort.MethodsWe conducted a retrospective review of 90 patients with HER2-positive early-stage breast cancer treated with adjuvant trastuzumab (Herceptin®, Herzuma®, or Kanjinti®) between January 2020 and January 2025 at Queen Mary Hospital, Hong Kong. Cardiac monitoring was performed via multi-gated acquisition (MUGA) scans every three months. Cardiotoxicity was defined as a ≥10% absolute decline in left ventricular ejection fraction (LVEF), LVEF <50%, or symptomatic heart failure. The primary study endpoint was time to cardiac event.ResultsCardiac events occurred in 19 patients (Herceptin®:18.6%, Herzuma®: 19.4%, Kanjinti®: 36.4%). No statistically significant differences in time to cardiac event were observed (log-rank p > 0.20). The odds ratio for events was highest in the Kanjinti® group (vs. Herceptin®, OR = 2.50, p = 0.24). Median time to event was shortest in the Kanjinti® group. No significant associations between cardiac events and cardiovascular risk factors identified.ConclusionTrastuzumab biosimilars demonstrated comparable short-term cardiac safety to reference trastuzumab. While a higher event rate was observed in the Kanjinti® group, the small sample size limits interpretation. Prospective studies with longer follow-up and larger patient number are warranted to better characterize long-term cardiac outcomes.